Homosemiosis, mimicry and superficial similarity: notes on the conceptualization of independent emergence of similarity in biology - Kleisner, Karel (Theory in biosciences, 2008)
Independent phenotypic emergence of superficially similar traits is a phenomenon frequently reported from investigations in the whole biota. Superficial similarity (including mimicry) is frequently explained as results of selective forces (predation or external environment). However, the mechanisms underlying independent (polyphyletic) emergence of similar phenotypic features remain largely unknown. A part of superficial similarity may emerge due to the occasional re-activation of latent genetic and/or developmental precursors. A specific kind of superficial similarity is represented by the phenomenon of mimicry that presupposes the attendance of a particular animal-interpreter. Despite diversity of ways how mimetic patterns are generated, they are structurally similar and often bear a common semantic message for an interpreter (predator); therefore, the term "homosemiosis" is proposed for such cases of sign-mediated correspondences where congruence of meaning appears.
Keywords: modely genetické; Developmental Biology; Insecta; vývojová biologie; Animals; Models, Genetic; hmyz; zvířata